Computational Design and Toxicity Prediction of Oxazole Derivatives Targeting PPARγ as Potential Therapeutics for Diabetes Mellitus in Compare to Rosiglitazone and Pioglitazone - Rashid, Mohammad Rashid; Husain, Asif; Mohammad Ajmal; Mausin Khan; Sana Hashmi (Journal of the Chilean Chemical Society, 2024)
The goal of this research is to investigate new oxazole derivative from designed series (A1-7; B1-8 & C1-8) in order to find new drug molecules for treatment of Diabetes Mellitus (DM). The PPAR receptor was chosen as the target of molecular docking investigations, which were executed using PyRx software. In silico analyses, including physicochemical properties, drug score, drug likeness, solubility, and toxicity prediction, were conducted using software such as Swiss ADME, Osiris property explorer, Lipinski filter and Toxtree method. All molecules passed the Lipinski rule with the zero violations and synthetic score was also found to be in the easy limit. All ligands showed drug score values ranging from 0.11 to 0.9 (no negative value). Compounds A6, C2, C5, C6, C7 and C8 were shown drug score from 0.91 to 0.80, which is closer to 1 and therefore considered as druggable ligands, when compared with the standard drug, Rosiglitazone and Pioglitazone also found non-toxic. All compounds shown logP values between -0.25 to 4.58. The RMSD value of receptor and receptor-ligand complexes was analyzed, and it revealed the stability of binding interactions and remained stable throughout the simulation. Compound C8 was found highest RMSD score (67.34Å) in compare to other compounds and standard drug Rosiglitazone (64.31Å). The TPSA were found within the range 35.26 to 128.60 and MR also were in the range 32.21-113.62. Compounds were found to be non-substrate for p glycoprotein except C4, high GIA% (>90%), also displayed negative permeability across the BBB, and most of compounds were found inhibitor of CYP 1A2 and CYP 2C19 and non-inhibitor of CYP 2C9, CYP 2D6 and CYP 3A4. Compound C5 was exhibited higher drug score (0.91), bioactivity score and revealed good drug relevant properties, ADME and no toxicity profile in compared to other ligands and standard drugs. The most active compound of the series was found C5 and C8 therefore further studies on this compound continue in our research laboratory to acquire more information about SAR and QSAR. Finally, it is conceivable that further derivatization of these compounds could result in obtaining more selective lead compounds.